Shortcomings and proposed reforms in the existing shariah governance of islamic banking - Abdulazeem Abozaid (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
Since its inception a few decades ago, the Islamic banking and finance industry has been self-regulated with regards to Shariah governance. Despite the existence of certain regulatory authorities from within the industry, such as Accounting and Auditing for Islamic Financial Institutions (AAOIFI) and Islamic Financial Services Board (IFSB), none of their resolutions or standards are effectively binding. Few countries have enforced some rules related to Shariah-governance. Still, in most cases, these rules did not go beyond the requirement of formulating Shariah controlling bodies, which is practically left to the banks themselves. Islamic banks are almost left to choose or dismiss their Shariah controllers, and no clear criteria are set by any authority to ascertain the proper qualifications of the Shariah controllers. Moreover, some of the Shariah standards and fatwas are found to conflict with the established resolutions issued by Fiqh academies. These matter point to the deficiencies in the existing Shariah governance and hence the need to address them.